Avaliação do efeito anticâncer de naftoquinonas sintéticas em modelo de leucemia mielóide aguda - Lima, Ana Beatriz da (2025)
Cancer, including acute myeloid leukemia (AML), remains a major cause of global mortality, highlighting the urgent need for innovative and targeted therapies. In this study, we initially investigated the cytotoxic effects of naphthoquinone derivatives in a panel of different tumor cell lines. Among them, the HL60 cell line was selected as an experimental model of acute promyelocytic leukemia, with the molecules LC04 and LC14 standing out due to their high therapeutic potential. Cell viability (Alamar Blue), membrane integrity (propidium iodide), cell cycle analysis, scanning electron microscopy (SEM), reactive oxygen species (ROS) production, and gene expression (RT-qPCR) assays were performed. Data were expressed as mean ± SEM or IC50 with a 95% confidence interval, obtained through nonlinear regression. Quantitative analyses were based on three independent experiments, and statistical significance was determined using ANOVA, followed by Bonferroni or Tukey post hoc tests (p < 0.05), using Prism 5.0 software (GraphPad Software). The results showed that LC04 and LC14 had IC50 values of 0.74 µM and 1.08 µM, respectively. Regarding the cell cycle, LC14 reduced the G0/G1 phase (34.40%) and increased the Sub-G1 population (13.60%), indicating DNA fragmentation, while LC04 induced G0/G1 phase arrest and decreased the S phase (22.30%). Both molecules caused morphological alterations observed by SEM, with LC14 inducing more severe cellular damage. In the ROS assay, LC04 and LC14 significantly increased oxidative stress levels after 3 h (12% and 15%, respectively) and 6 h (35% and 45%, respectively). Gene expression analysis revealed that LC14 downregulated BCL2 and upregulated BAX, while both molecules induced TP53 expression, with LC04 having a greater impact (p < 0.01). Additionally, LC14 upregulated H2AFX and downregulated PARP1, suggesting the induction of DNA damage. These findings reinforce the therapeutic potential of LC04 and LC14, highlighting their promising molecular characteristics.